The Roles of Exosomes in Immunoregulation and Autoimmune Thyroid Diseases - Zou, Junli; Peng, Huiyong; Liu, Yingzhao (Frontiers in Immunology, 2021)
Exosomes are extracellular microvesicles (30-150 nm) released from cells that contain proteins, lipids, RNA and DNA. They can deliver bioactive molecules and serve as carriers facilitating cell-cell communication, such as antigen presentation, inflammatory activation, autoimmune diseases (AIDs) and tumor metastasis. Recently, much attention has been attracted to the biology and functions of exosomes in immune regulation and AIDs, including autoimmune thyroid diseases (AITDs). Some studies have shown that exosomes are involved in the occurrence and development of AITDs, but they are still in the preliminary stage of exploration. This review mainly introduces the association of exosomes with immune regulation and emphasizes the potential role of exosomes in AITDs, aiming to provide new research strategies and directions for the pathogenesis and early diagnosis of AITDs.